Pc pentaquarks with chiral tensor and quark dynamics - Yamaguchi, Yasuhiro (2020)
We investigate the hidden-charm pentaquarks as superpositions of Λc͞D⁽*⁾ ðÞ and Σc⁽*⁾͞D⁽*⁾(isospin I = 1/2) meson-baryon channels coupled to a uudc͞c compact core by employing an interaction satisfying the heavy quark and chiral symmetries. Our model can consistently explain the masses and decay widths of Pc⁺(4312), Pc⁺(4440) and Pc⁺(4457) with the dominant components of Σc͞D and Σc͞D* with spin-parity assignments Jᴾ =1/2⁻, 3/2⁻ and 1/2⁻, respectively. We analyze basic properties of the Pc’s such as masses and decay widths, and find that the mass ordering is dominantly determined by the quark dynamics while the decay widths by the tensor force of the one-pion exchange.